1996
DOI: 10.1093/bja/76.4.519
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of commonly used plasma substitutes during preoperative normovolaemic acute haemodilution

Abstract: Preoperative normovolaemic acute haemodilution (PNAH) is used to reduce major blood loss during elective surgery. Considerable attention has been paid to colloid osmotic pressure, index of diffusibility and intravascular half-life of the currently available substitutes, but there is little information on their rheological properties from in vivo studies. Forty patients undergoing elective aortic reconstruction were given 4% human albumin (HA), 3.5% dextran 40 (Dxt 40), 6% dextran 60 (Dxt 60), 6% hydroxyethylst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0
3

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 19 publications
3
21
0
3
Order By: Relevance
“…Similar results have been reported by other authors with HES, MFG and albumin [14,15]. Both colloids decreased hemoglobin concentration by the same amount and increased cardiac index.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results have been reported by other authors with HES, MFG and albumin [14,15]. Both colloids decreased hemoglobin concentration by the same amount and increased cardiac index.…”
Section: Discussionsupporting
confidence: 91%
“…Explanations for these differences include improved haemorheology and reduced renal arteriolar vasoconstrictor release with HES solutions, or a reduction in renal capillary leak. HES 200/0·62 has been shown to reduce whole blood viscosity compared with gelatine during aortic surgery 15 . Since then, it has been shown that smaller molecules of starch reduce erythrocyte aggregation by preventing the bridges formed by macromolecules such as fibrinogen and large HES molecules 16 .…”
Section: Discussionmentioning
confidence: 99%
“…However, no significant differences after hemodilution with HES 650/0.42 as compared with HES 130/0.42 have been observed by relating the decrease in hemoglobin concentration to the measured HES in vivo molecular weights ( fig. 6F) 26,27 The predominant rheologic effect of colloids consists in the reduction of whole blood viscosity proportional to the magnitude of their plasma volume expansion. 27 Plasma viscosity, however, is determined principally by the number and physical properties of dissolved macromolecules.…”
Section: Discussionmentioning
confidence: 99%